Stategi Pemasaran Digital Sebagai Pengembangan Usaha Minuman Fungsional “Onspot” di Kota Pekanbaru - Jum'atri Yusri; Evi Rossi; Angga Pramana; Yelmira Zalfiatri; Ramayuni Ramayuni; Rusli Rustam (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
ONSPOT is a business owned by students of the Department of Agricultural Product Technology, Faculty of Agriculture, Riau University. This business is engaged in the contemporary beverage with the main ingredients of functional food yogurt and kefir. ONSPOT's business development received funding for activities through the University Student Entrepreneur Competition (KMP) activity in 2020 for the business development category. It is believed that this business prospect is quite promising in the future considering that ONSPOT products carry contemporary beverage products containing good bacteria that have an impact on health and have a good taste. However, the great potential that ONSPOT has to develop its products is not followed by an optimal marketing and branding process, where the marketing process is still carried out through communication from one person to another and through Instagram. The branding process is still constrained by minimal information. This causes the limitations of ONSPOT to be widely known by the public. Entrepreneurship development service activities by conducting training on ONSPOT website management and optimizing ONSPOT social media, so that ONSPOT appeals are increasingly recognized by the public